Eternity clauses in democratic constitutionalism - Suteu, Silvia (Oxford : Oxford University Press, 2021)
This monograph examines unamendable provisions of constitutions, known as eternity clauses, and the challenges they present to democratic constitutionalism. The book explores the role of eternity clauses in constitution-making, constitutional adjudication, and constitutional reform and posits an ambiguous legacy for eternity clauses.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 27, 2021).
Keywords: Constitutional amendments; Democracy